A Case of Esophagopericardial Fistula as a Complication of Upper Gastro-Intestinal Endoscopy - Ofoegbu, Chima K. P. (Medknow Publications & Media Pvt Ltd, 2014)
A case of suppurative pericarditis from an esophagopericardial fistula (EPF) following the upper gastrointestinal endoscopy (UGIE). A 38-year-old schizophrenic male patient with gastro-esophageal reflux disease (GORD) and previously dilated esophageal stricture was presented with acute retrosternal chest pain. The patient pulled out the endoscope during UGIE the previous day. A barium swallow (BS) post endoscopy was normal. The patient was initially hemodynamically stable and cardiac evaluation was normal. The patient subsequently developed features of cardiogenic shock. Echocardiography confirmed pericardial effusion and pericardial aspiration yielded pus. Surgical drainage with pericardial tube insertion was done. Pericardial biopsy revealed acute suppurative inflammation with food particles. The patient continued with antibiotics and pericardial drainage for 14 days and repeat BS and chest computerized tomography scan revealed no EPF. The patient was discharged 24 days after the presentation and remained well at follow-up. A rare, serious complication of UGIE which may be easily missed and is associated with a high mortality with delayed treatment.